The Integrating STEM in Hooke's Law and Elasticity Worksheets: Enhancing Student Collaboration and Learning Outcomes - Dian Pertiwi Rasmi; Syifa Salsabila Wibisana; Menza Hendri (Jurnal Penelitian Pendidikan IPA, 2025)
One of the goals of physics learning is to help students develop collaboration skills. A preliminary study conducted showed that resulting in less than optimal learning outcomes. Such a learning process causes the development of students' collaboration skills to be less stimulated properly. This study aims to determine the effect of web-based worksheets based on STEM integrated problems on students' collaboration skills. The research method uses a quasi-experimental technique with one group pretest-posttest design. The sample was selected using a purposive sampling strategy. The samples involved were 36 students in class F7 of SMA Negeri 1 Kota Jambi. The test was conducted to collect data on students' collaboration skills and student learning outcomes. The research data were collected using a questionnaire of ten questions and a ten-item multiple-choice test that was valid with a reliability coefficient of 0.70. That there was a significant difference between the learning outcomes of students in the pretest and posttest with a sig. (2-tailed) <0.05, which indicates that the STEM-integrated Elasticity and Hooke's Law worksheet has a positive effect on students' critical thinking skills. With an N-Gain score of 0.76 in the high category, the STEM-integrated physics web worksheet on the Elasticity and Hooke's Law material can improve students' collaboration skills.